Implementasi Model Pembelajaran Tematik Scientific dalam Meningkatkan Minat Belajar Peserta Didik - Rusni Walangadi (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2019)
This paper discusses the other side of the application of scientific thematic learning models in increasing the learning interest of students at SDN 2 Kabila, Bone Bolango Regency. The method used is descriptive qualitative. Thematic Learning by: (a) student-centered, (b) Giving participants directly to students, (c) using invisible subjects, (d) presenting different subject concepts from the learning process, (e) flexible protection, (f) learning outcomes can be developed according to the interests and needs of students. The factor hampering the application of thematic learning models in scientific discussion is the overcrowding of material available in each theme, so that the determined time is deemed inadequate by the teacher. Efforts made by teachers are to do additional hours of study Exit school hours of learning, as well as ask for time allowances on teachers of religious subjects, and sports.